Synthesis and Analytical Applications of a New Heterocyclic Bis-azo Dye: 2,6-bis(7-Hydroxyacenaphthyl-8-Azo)Pyridine - Singh, Ishwar; K. Sharma, Ashok; Singh, Devender; K. Yadav, Sanjiv (Asian Journal of Chemistry, 2010)
A new heterocyclic bis-azo dye, 2,6-bis(7-hydroxyacenaphthyl-8- azo)pyridine (PBA) has been synthesized, which gives sensitive colour reactions with four metal ions. Reaction behaviour of this reagent with these metal ions, viz., copper(II), zinc(II), cadmium(II) and mercury(II) has been established under various conditions. All of these metal ions form 1 : 2 complex (M : L) with the reagent. The molar absorptivities of the colour reactions are 4.2 x 104 L mole-1 cm-1 for copper λmax 526 nm), 5.0 x 104 L mor-1 cm-1 for zinc (λmax 520 nm), 2.2 x 104 L mor-1 cm-1 for cadmium (λmax 524 nm), 4.0 x 104 L mol-1 cm-1 for mercury (λmax 520 nm). Other physico-chemical characteristics of the complexes are established spectrophotometrically. A number of foreign ions tested for their interference and the use of masking agents wherever necessary is tabulated. Copper(II) can be determined selectively with PBA and the recommended procedure has been applied to estimate copper levels in food and milk samples.